A Revi[e]w of anti-poverty evaluation programmes (Nabakrushna Choudhury Centre for Development Studies, 1980)
Part 2 covers six districts of Orissa: Sambalpur, Koraput, Keonjhar, Puri, Ganjam, and Kalahandi.